UNDERSTANDING ISLAMIC EPISTEMOLOGY IN THE DEVELOPMENT OF LEGAL SCIENCE - Pramushinta, Azzimar Shidqy; Wahyuningsih, Sri Endah (Jurnal Hukum Khaira Ummah, 2023)
Islamic epistemology, or initially better known as the Philosophy of Islamic Law, is basically a new science born long after the establishment of other Islamic sciences. Islamic epistemology gives Muslims more insight into how to philosophize in the way of Islam. This study aims to understand about what is Islamic Epistemology as well as the historical development of Islamic Epistemology. In addition, this study also aims to find out what are the sources of law used in Islamic Epistemology. The method used in this research is the normative juridical method, which is focused to examine the application of rules in positive law. Data of research results that have been obtained and processed, presented in the form of descriptive narrative. The results show that Islamic Epistemology is a branch of the Philosophy of Science and the history of the development of Islamic Epistemology has begun since the time of the Greek philosophers who started by Al-Asy'ari. The sources of law used in Islamic Epistemogy are: Qur'an, As Sunnah, Ijma, and Qiyas.Keywords: Islamic Epistemology, Philosophy, Law Science